Proyecto de Factibilidad para la creación de una empresa productora y comercializadora de chicharrón de queso en Gonzanamá, provincia de Loja - Aguirre Ochoa, Diana Vanessa (2024)
This project is carried out with the objective of determining the feasibility of creating a company that produces and markets cheese crackling, in the Gonzanamá canton, Province of Loja. The research approach was mixed, taking into account that both qualitative and quantitative information was collected. The methods used were inductive, deductive and descriptive. The research techniques applied were bibliographic, direct observation and survey. The survey questionnaire was used as an instrument for collecting information, which was applied to the demand for the product and the suppliers that exist in the area. The results of the survey show that 70% of families consume cheese crackling, consuming 1 to 2 pounds per week. To meet unsatisfied demand, the company will have an installed capacity for the production of 9.800 250 ml containers per month, reaching an annual production of 117.600 units, which is equivalent to 36,94% of unsatisfied demand in 2024. To launch the project, an initial investment of $35.909,17 is required, which is expected to be recovered in 1 year, 3 months, 18 days. Through the financial evaluation, the feasibility of the project was determined, taking into account that the NPV is $ 126.406,53 and the IRR is 49,86%, the Benefit Cost Ratio is 1.15.